Model of series queues networks for passenger at Basra International Airport (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Large networks of queue systems represent important systems in the real world such as patients in hospital, calls in call centers, shipping containers in a seaport, and passenger terminals at airports. n this study, we deal with bottlenecks in the   series queues networks in the passenger terminal before entering the stage of departure and boarding, and to know the size and absorption that passengers can reach at Basra International Airport. The search was represented statistically by studying the networks of series queues to reduce the waiting time for service performance by using statistical program packages R, as it is one of the latest and most accurate methods ,as well as the lack of calculations. Through the results, it was concluded that there are no bottlenecks at the present time for the lack of travelers due to the Corona pandemic, and it is expected in the near or distant future to increase the number